Avaliação helmintológica de veados-catingueiros Mazama gouazoubira Fischer, 1817 (Cervidae: Odocoileini) de vida livre, procedentes do Pantanal brasileiro, com considerações sobre Pygarginema verrucosa (Molin, 1860) Kadenatzii, 1948 (Spirocercidae: Ascaropsinae) - Lux Hoppe, E. G. [UNESP] (2010)
The Brazilian Pantanal wetlands are a unique ecosystem with a faunistic composition similar to that of the adjacent biomes but in higher densities. The early establishment of domestic cattle husbandry in that area introduced pathogens that may influence the indigenous Pantanalian fauna. In this paper, the authors describe the helminthfauna of ten free-ranging adult Mazama gouazoubira from the Paiaguás sub-region, along with the descriptors of infection. Morphological description of Pygarginema verrucosa is supplied, with comments on other species of this genus. The helminth species found are similar to domestic cattle helminthfauna of the same physiographic region, suggesting an adaptation of bovine parasites to this host.